How will energy demand develop in the developing world? - Wolfram, Catherine (2012)
Argues that the world's poor and near-poor will play a major role in driving medium-run growth in energy consumption; and first-time purchases of long-lived durable goods such as refrigerators and cars will have substantial consequences for consumption and the emission of greenhouse gases.